2010
DOI: 10.1080/07391102.2010.10508587
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions between Arginines and the Minor Groove in the Nucleosome

Abstract: Proteins rely on a variety of readout mechanisms to preferentially bind specific DNA sequences. The nucleosome offers a prominent example of a shape readout mechanism where arginines insert into narrow minor groove regions that face the histone core. Here we compare DNA shape and arginine recognition of three nucleosome core particle structures, expanding on our previous study by characterizing two additional structures, one with a different protein sequence and one with a different DNA sequence. The electrost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 26 publications
(36 reference statements)
5
80
0
Order By: Relevance
“…Recently, an observed correlation between these two variables was interpreted as influence of nucleosome positioning on methylation patterning (45). However, electrostatic interactions between arginines and the minor groove occur in the nucleosome (22,47), and the minor groove narrowing associated with cytosine methylation could enhance these. The methylation patterns might therefore also be a partial determinant of nucleosome position, with methylated CpG dinucleotides giving rise to stronger electrostatic interactions with histones, increasing the stability of nucleosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an observed correlation between these two variables was interpreted as influence of nucleosome positioning on methylation patterning (45). However, electrostatic interactions between arginines and the minor groove occur in the nucleosome (22,47), and the minor groove narrowing associated with cytosine methylation could enhance these. The methylation patterns might therefore also be a partial determinant of nucleosome position, with methylated CpG dinucleotides giving rise to stronger electrostatic interactions with histones, increasing the stability of nucleosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that sprocket arginine-DNA contacts may play an important role in the rotational positioning of nucleosomes (Luger et al 1997;Harp et al 2000;Rohs et al 2009;Wang et al 2010;West et al 2010). For example, short poly(A) stretches narrow the DNA minor groove, potentially enhancing electrostatic interactions between the DNA phosphate backbone and the sprocket arginine (Rohs et al 2009;West et al 2010).…”
mentioning
confidence: 99%
“…Sprocket arginine residues are highly conserved (Muthurajan et al 2003;Sullivan and Landsman 2003), and the insertion of sprocket arginine side chains into the DNA minor groove comprises a significant fraction of the solvent accessible surface area that is buried upon histone-DNA binding (Davey et al 2002). Studies have suggested that sprocket arginine-DNA contacts may play an important role in the rotational positioning of nucleosomes (Luger et al 1997;Harp et al 2000;Rohs et al 2009;Wang et al 2010;West et al 2010). For example, short poly(A) stretches narrow the DNA minor groove, potentially enhancing electrostatic interactions between the DNA phosphate backbone and the sprocket arginine (Rohs et al 2009;West et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrostatic interactions between DNA and the histones contribute to the stability of the nucleosome [9,10], as well as of any formed superstructures such as the 30 nm filament [11,12,13]. During the last decade, or two, it has become clear that the functional roles of chromatin/nucleosomes/histones are much richer than being limited to that of compaction [14,15,16].…”
Section: Introductionmentioning
confidence: 99%